Assessing Differential Item Functioning in a Teacher Self-Assessment of Cultural Responsiveness. (October 2021) - Fallon, Lindsay M.; Cathcart, Sadie C.; Johnson, Austin H.
The Assessment of Culturally and Contextually Relevant Supports (ACCReS) was developed in response to the need for well-constructed instruments to measure teachers' cultural responsiveness and guide decision-making related to professional development needs. The current study sought to evaluate the presence of differential item functioning (DIF) in ACCReS items and the magnitude of DIF, if detected. With a national sample of 999 grade K-12 teachers in the United States, we examined measurement invariance of ACCReS items in relation to responses from (a) racially and ethnically minoritized (REM) youth and white teachers (teacher race), (b) teachers in schools with 0–50% and 51–100% REM youth (student race), and (c) teachers with <1–5 years of teaching experience and teachers with >5 years of experience. Findings suggested that ACCReS items exhibited negligible levels of DIF. The lack of DIF found provides additional evidence for the validity of scores from the ACCReS to assess teachers' cultural responsiveness. Furthermore, descriptive analyses revealed that teachers were more likely to agree with items pertaining to their own classroom practice than items related to access to adequate training and support. Results inform implications for future educational and measurement research.